Qualitative and physical-chemical indicators of chitosan samples and their comparative characteristics with imported analogues - O. V. Pavlova; S. S. Anufrik; E. I. Eisymont; M. M. Trusova (Современная наука и инновации, 2025)
The work is devoted to the study of the qualitative and physicochemical indicators of chitosan obtained by acid-base hydrolysis and enzymatic hydrolysis, and their comparative characteristics with an imported analogue. The introduction identifies the problem in the field of obtaining and using technological auxiliary materials in the beverage industry. The scientific task is to compare the experimentally obtained technological auxiliary materials (chitosan with a deacetylation degree of 62%, insoluble in 1% solutions of organic acids, chitosan with a deacetylation degree of 98%, soluble in 1% solutions of organic acids and imported chitosan (China) in order to obtain import substitution. Classical methods of physicochemical analysis were used as materials and methods to determine the concentration of chemical elements in chitosan samples, a statistical analysis method. It was found that a chitosan sample with a deacetylation degree of 98% has a structure similar to the structure of chitosan produced in China, chitosan with a deacetylation degree of 62% has an amorphous-crystalline structure. In conclusion, a conclusion was made about the compliance of the quality of the obtained samples with the reference chitosan, about the prospects for using chitosan in technological processes taking into account its structural features.